Perception of Filipino sports journalists on the use of artificial intelligence in their field - Guzman, Justin Peter Quicho; Khan, Rachel E. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2025)
Artificial intelligence is a relatively new form of technology that aims to automate tasks, effectively making work easier to do. This is very much apparent in the field of sports journalism, wherein numerous types of artificial intelligence have risen as a supposed aide to the work of a sports journalist. But with this unfamiliar territory looming for sports media, there then exists a need to find out how sports journalists feel about it.
As such, this study focused on the perception of Filipino sports journalists on the use of artificial intelligence and its many forms in their work. Guided by both the Diffusion of Innovation theory and the Uses and Gratifications theory, it reviewed and analyzed interview answers from seven sports journalists currently in the industry, all about their opinions on AI, its role in their work, and their thoughts on its future in the field.
The findings revealed that Filipino sports journalists generally accept and see the role of AI in the industry, but it has to stay in an assistive role rather than an overtaking one. It helps out in huge chunks of work such as transcription and translation, but journalists say that they draw the line at AI actually doing their work for them.
This study has implications for media organizations looking to integrate artificial intelligence into their work. With this study, they may better analyze the media’s state of knowledge and implement their guidelines on AI in a more appropriate way.
Thesis
Includes bibliography
Keywords: Sports journalism -- Philippines; Journalism -- Technological innovations; Sports -- Technological innovations -- Philippines